POVERTY AS A GLOBAL PROBLEM - Babayeva Sabinabonu Davronbek qizi (World Scientific Research Journal, 2025)
Annotation: Poverty remains one of the most pressing global challenges of the 21st century, affecting all aspects of societal development. This article explores the root causes and manifestations of poverty, its implications for sustainable development, and the most effective international strategies for combating it. Particular attention is given to social programs, infrastructure development, and support for small and medium-sized enterprises as key pillars of a comprehensive approach. The article also highlights the role of international organizations and the importance of investment in human capital.